Burnout syndrome in resident physicians: A study after the third COVID-19 wave in two tertiary hospitals of southeastern Brazil - Aline Camile Yehia; Janaina Moreira; Melissa Orlandin Premaor (PLoS ONE, 2025)
Background In recent years, there has been an increase in the concern for the mental health of resident physicians. The COVID-19 pandemic may have further contributed negatively to the mental health of this population. Objectives We aimed to evaluate the probability of Burnout Syndrome in resident physicians involved in COVID-19 care services during the Pandemic and possible factors associated with it. Methods A cross-sectional study was conducted in two tertiary hospitals in Belo Horizonte, Brazil, between the 5th of June and the 14th of September 2022. A survey including the instruments Oldenburg Burnout Inventory (OLBI), Depression, Anxiety and Stress Scale (DASS-21), Patient Health Questionnaire (PHQ-9), and the Brief Resilient Coping Scale (BRCS) was applied. Results From the 181 resident physicians invited to participate, 104 agreed. The mean age (SD) was 29.9 (3.3) years; 56.7% were female, and 67.3% were from a clinical residency program. The score of the OLBI was high. In the multivariate analysis, being single, using psychiatric medications, and taking direct care of COVID-19 were associated with increases in the OLBI scale scores. The frequencies of probable depression and anxiety assessed by DASS-21 were 15.3% and 5.7%, respectively. Notwithstanding, the frequency of probable stress was 61.5%. Depressive symptoms, as evaluated by the PHQ-9 questionnaire, were highly prevalent at 61.5%. Further, 29% of the resident physicians interviewed in our study had probable low resilience according to the BRCS score. Conclusion The frequency of Burnout, depression, and stress found in our study appears to be relevant in the resident physicians.